Neuroparenting in Muslim and Catholic Children's Interactions at Dulur Ulin Festival - Andini, Andini; Siswanto, Mikael Adi; Rosyad, Rifki (UIN Sunan Gunung Djati Bandung, 2025)
Encounters between religious communities are the gateway to knowing, understanding and tolerance. This was done by Catholic children from Joy Kids International Tasikmalaya Elementary School who visited the Darussalam Ciamis Islamic Boarding School. This encounter is packaged through the